(untitled) (Revista Brasileira Multidisciplinar, 2026)
Introduction: Leptospirosis is an infection caused by the Leptospira bacteria, found in the urine of rodents. During floods, these bacteria can spread easily due to their capacity for dissemination, contaminating water, food, and other objects, thereby increasing the risk of infection. Objective: This study describe the epidemiology, the morbidity and mortality of leptospirosis in the state of Rio Grande do Sul, before and after the floods, in the year of 2024. Methodology: An ecological time series study using secondary data from the Departamento de Informática do Sistema Único de Saúde (DATASUS) obtained from the Sistema de Informação de Agravos de Notificação (SINAN). Results and Discussion: The study found that the floods in Rio Grande do Sul led to an 82.19% increase in leptospirosis cases between January and May 2024, compared to 2022 and 2023. The disease, which is endemic, can become epidemic during extended periods of rainfall. The majority of cases occurred among men, due to occupational exposure, with a predominance among white individuals, reflecting the state’s demographic profile. The most affected age group was from 20 to 59 years, the economically active class. Conclusion: For control and prevention, the study suggests the importance of educational campaigns and awareness programs to reduce vulnerability in future environmental disasters.